Phonological Processing and Word and Non-Word Reading Ability among Farsi-Speaking Children with Cochlear Implants, Hearing Aids and Normal Hearing - Elham Masoumi; Asghar Haghjoo; Zahra Soleymani (Auditory and Vestibular Research)
Background and Aim: Individuals who suffer Hearing Loss (HL) from inefficient auditory input will experience difficulty in phonological processing and reading. This study aimed to investigate the phonological processing and word and non-word reading abilities of Farsispeaking children with Cochlear Implants (CIs), Hearing Aids (HAs) and Normal Hearing (NH). Methods: Sixty-three children with severe to profound HL and NH who were in the first grade participated. Phonological Awareness (PA) and Phonological Working Memory (PWM) tests were used to assess phonological processing. Word and non-word reading abilities were assessed through reading and dyslexia tests reading abilities, phonological processing as well as the correlation between them were compared among three groups. Results: The PA, PWM and reading abilities of NH children were significantly different from children with HL (p<0.01). Correlations between words and non-words reading ability and some phonological processing tasks were observed in each of the three groups. Phonemic awareness for all three groups and intra-syllabic awareness for children with HA and NH were the most important predictors for word and non-word reading abilities. Conclusion: Hearing impairment had a critical effect on phonological processing as an important factor in word and non-word reading.